Formulation and evaluation of sensory characteristics of functional food 'Ceremoringa Bar' made from moringa leaves (Moringa oleifera) - Dian Shofiya; Inne Soesanti; Nur Rahman; Lohita Adinda Rahmadani; Ade Riezma Amrina Rosyida (AcTion: Aceh Nutrition Journal, 2026)
The success of breastfeeding is mediated by several variables, including maternal nutritional status. Moringa oleifera leaves are a nutrient-rich, locally available food source that may be cultivated as a functional snack for the maternal diet during pregnancy and lactation. Moringa dietary snack foods with acceptable sensory attributes are still limited in the market. This study attempted to produce a functional food product from moringa leaves (Ceremoringa Bar) and evaluate its sensory behavior for possible formulations with suitable acceptance. This experimental laboratory study was conducted at the Poltekkes Kemenkes Surabaya Food Processing Laboratory between August and October 2025. Nine Ceremoringa moringa formulations were prepared according to three processing processes (no heating, cooking without water addition, and cooking with water addition) added to dried apple, papaya, or strawberry. Sensory evaluation was conducted by 25 trained panelists using a 5-points hedonic scale covering color, aroma, taste, and texture. Data analysis relied on the Friedman test, followed by the Wilcoxon signed-rank test with Bonferroni correction. The participants assessed the sensory attributes significantly differently (p < 0.05). Post-hoc analysis was performed but found no differences between the formulation pairs. Formulation 3C also appeared to have the highest consistency of sensory acceptance, especially regarding texture, based on median and interquartile range assessments. In conclusion, Ceremoringa Bar displayed good sensory tolerance and can be used as a moringa-based functional snack to aid maternal nutrition. However, its biological effects on lactation have not yet been measured.